Different impacts of magnesium on the catalytic activity of exchangeable calcium in coal gasification with CO2 and steam. (15th April 2020) - Yu, Ge; Yu, Dunxi; Liu, Fangqi; Han, Jingkun; Yu, Xin; Wu, Jianqun; Xu, Minghou
Highlights: Impacts of Mg on Ca catalysis are studied in CO2 - and steam-coal gasification. While Mg promotes Ca catalysis in CO2, it depresses it in steam. Impacts of Mg on Ca catalysis are more pronounced at 800 ℃. Mechanisms for the different impacts of Mg on Ca catalysis are presented. Abstract: Exchangeable calcium (Ca) in coal has excellent catalysis on gasification reaction. Magnesium (Mg) may have effects on this process, but the previous researches are limited and the influence mechanism is still unclear. Thus, this work aims to investigate the influence of Mg on Ca catalytic gasification process. A low-rank coal was demineralized and then loaded with Ca and Mg, separately or jointly, by ion exchange. Subsequently, the samples were gasified in CO2 or steam at 800 ℃–900 ℃ in a specially designed thermogravimetric reactor. The partially-gasified chars were collected and analyzed with scanning electron microscopy (SEM), X-ray diffraction (XRD), N2 adsorption tests, and temperature-programmed desorption (TPD) with a mass spectrometer (MS). The results show that the exchangeable Ca and Mg in coal form Ca-containing particles (CaCO3 or CaO) and MgO particles, respectively. Moreover, Mg has different impacts on the catalytic activity of Ca during CO2 and steam gasification. In CO2, Mg has a promoting effect. It is rather evident at 800 ℃, resulting from that MgO inhibits the sintering of large CaCO3 particles. These particles are mainly on the char surface and the pore structure is less developed. On the contrary, in steam, Mg has an inhibiting effect. It reduces the calcium-carbon interface and inhibits the channeling reaction process.